2020
DOI: 10.1111/ijcp.13554
|View full text |Cite
|
Sign up to set email alerts
|

The effect of subclinical hypothyroidism on body composition parameters in children

Abstract: Background It's known that overt hypothyroidism increases body fat content and weight. There's limited research about the effect of subclinical hypothyroidism (SH) on body composition in children and the effect of LT4 treatment. We aimed to evaluate body composition parameters in healthy subjects and in children with mild SH (MSH) and determine the effect of LT4 treatment. Methods Sixty‐four healthy children and 32 children with MSH were included. Anthropometric measurements and hormonal parameters were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
3
1
0
Order By: Relevance
“…In addition, hypothyroid subjects showed increased head circumference, zygomatic width, nasal base width, intercommissural distance, cranial base length, and maxillary and mandibular length. These findings accord with those reported by Gunes et al ( 2020 ), which suggest that hypothyroid individuals could present early changes in body composition parameters. In contrast, our results diverge from those of Vucic et al ( 2017 ), who reported an association between hypothyroidism and decreased maxillary and mandibular growth, which could result in teeth impaction or delayed tooth eruption (Wassner 2017 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, hypothyroid subjects showed increased head circumference, zygomatic width, nasal base width, intercommissural distance, cranial base length, and maxillary and mandibular length. These findings accord with those reported by Gunes et al ( 2020 ), which suggest that hypothyroid individuals could present early changes in body composition parameters. In contrast, our results diverge from those of Vucic et al ( 2017 ), who reported an association between hypothyroidism and decreased maxillary and mandibular growth, which could result in teeth impaction or delayed tooth eruption (Wassner 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies also indicate a relationship between overweight/obesity and bone growth stimulation (Dimitri 2019 ; Zhu 2017 ). Our findings on craniofacial growth at peak growth in patients with overweight/obesity are in agreement with other investigations, which reported a more sagittal position of pogonion, leading to prognathism (Danze et al 2020 ), an increased longitudinal facial length (Cuccia et al 2007 ), and early eruption in both dentitions (Sánchez et al 2010 ). Finally, zygomatic width was significantly smaller in non-syndromic hypogrowth patients than in healthy subjects, which aligns with the findings from Attanasio and Shalet ( 2007 ) and Oliveira-Neto et al ( 2011 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Body composition is usually evaluated by using BIA (bioelectric impedance analysis), which calculates total body water (TBW) and fat-free body mass (FFM) without causing any fluid or electrolyte abnormalities [26,27]. Hypothyroidism is characterized by an increase in body fat, besides a relatively unaffected lean body mass component [28].…”
Section: Thyroid Function and Body Compositionmentioning
confidence: 99%